Marine gastropods at higher trophic level show stronger tolerance to ocean acidification. Issue 9 (30th June 2022) - Hu, Nan; Brönmark, Christer; Bourdeau, Paul E.; Hollander, Johan
Abstract : Climate change and anthropogenic activities are producing a range of new selection pressures, both abiotic and biotic, on marine organisms. Although it is known that climate change can differentially affect fitness‐related traits at different trophic levels of the food web, it is not clear if different trophic levels will respond via phenotypic plasticity in the form of maintenance of phenotypes in the face of abiotic and biotic environmental stress similarly. To answer this question, we combined a mesocosm experiment (120 days) using a food web comprising three gastropod species from two trophic levels (grazers and meso‐predators) and a meta‐analysis including 38 studies to address whether different trophic levels exhibit similar phenotypic responses to abiotic and biotic variables. Abiotic (ocean acidification) and biotic (predation) stress significantly influenced body mass, shell mass, shell thickness and shell strength in both grazers and meso‐predators in the mesocosm experiment, with the magnitude of OA effects greater on the meso‐predator than the grazers; a result supported by the meta‐analysis. In contrast, both mesocosm experiment and meta‐analysis found that predation risk induced stronger responses in shell morphology for grazers compared to meso‐predators. Together, our findings indicate that higher trophic level species are better able to maintain aspects of their phenotype under OA, suggesting that they may show greater tolerance to climate change effects in general, while lower trophic levels express higher levels of plastic inducible defences to maintain function when under threat of predation. By using marine snails as a model, our study provides new knowledge for understanding how changing environmental conditions may alter biological interactions, and increases our understanding of how climate change may affect ecological communities in which gastropods play a key role.